Mapping knowledge landscapes and research frontiers of gastrointestinal microbiota and bone metabolism: a text-mining study - Wu, Haiyang; Sun, Zaijie; Guo, Qiang; Li, Cheng (Frontiers in Cellular and Infection Microbiology, 2024)
Extensive research efforts have been dedicated to elucidating the intricate pathways by which gastrointestinal microbiota and their metabolites exert influence on the processes of bone formation. Nonetheless, a notable gap exists in the literature concerning a bibliometric analysis of research trends at the nexus of gastrointestinal microbiota and bone metabolism. To address this scholarly void, the present study employs a suite of bibliometric tools including online platforms, CiteSpace and VOSviewer to scrutinize the pertinent literature in the realm of gastrointestinal microbiota and bone metabolism. Examination of the temporal distribution of publications spanning from 2000 to 2023 reveals a discernible upward trajectory in research output, characterized by an average annual growth rate of 19.2%. Notably, China and the United States emerge as primary contributors. Predominant among contributing institutions are Emory University, Harvard University, and the University of California. Pacifici R from Emory University contributed the most research with 15 publications. In the realm of academic journals, Nutrients emerges as the foremost publisher, followed closely by Frontiers in Microbiology and PLOS One. And PLOS One attains the highest average citations of 32.48. Analysis of highly cited papers underscores a burgeoning interest in the therapeutic potential of probiotics or probiotic blends in modulating bone metabolism by augmenting host immune responses. Notably, significant research attention has coalesced around the therapeutic interventions of probiotics, particularly Lactobacillus reuteri, in osteoporosis, as well as the role of gastrointestinal microbiota in the etiology and progression of osteoarthritis. Keyword analysis reveals prevalent terms including gut microbiota, osteoporosis, bone density, probiotics, inflammation, SCFAs, metabolism, osteoarthritis, calcium absorption, obesity, double-blind, prebiotics, mechanisms, postmenopausal women, supplementation, risk factors, oxidative stress, and immune system. Future research endeavors warrant a nuanced exploration of topics such as inflammation, obesity, SCFAs, postmenopausal osteoporosis, skeletal muscle, oxidative stress, double-blind trials, and pathogenic mechanisms. In summary, this study presents a comprehensive bibliometric analysis of global research on the interplay between gastrointestinal microbiota and bone metabolism, offering valuable insights for scholars, particularly nascent researchers, embarking on analogous investigations within this domain.